2005
DOI: 10.1074/jbc.m505332200
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Evidence for Bacillus subtilis PaiA as a Novel N1-Spermidine/Spermine Acetyltransferase

Abstract: Bacillus subtilis PaiA has been implicated in the negative control of sporulation as well as production of degradative enzymes. PaiA shares recognizable sequence homology with N-acetyltransferases, including those that can acetylate spermidine/spermine substrates. We have determined the crystal structure of PaiA in complex with CoA at 1.9 Å resolution and found that PaiA is a member of the N-acetyltransferase superfamily of enzymes. Unexpectedly, we observed the binding of an oxidized CoA dimer in the active s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
85
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(92 citation statements)
references
References 40 publications
7
85
0
Order By: Relevance
“…We observed that Spm degradation occurred faster than Spd degradation, supporting previous studies suggesting a reduction in Spm during the natto fermentation process (Kobayashi et al, 2016(Kobayashi et al, , 2017. Spm has been reported to be the preferred substrate for SSAT (Forouhar et al, 2005;Woolridge et al, 1999). From these data, nutrient conditions appear to influence polyamine degradation by B. subtilis (natto).…”
supporting
confidence: 79%
See 1 more Smart Citation
“…We observed that Spm degradation occurred faster than Spd degradation, supporting previous studies suggesting a reduction in Spm during the natto fermentation process (Kobayashi et al, 2016(Kobayashi et al, , 2017. Spm has been reported to be the preferred substrate for SSAT (Forouhar et al, 2005;Woolridge et al, 1999). From these data, nutrient conditions appear to influence polyamine degradation by B. subtilis (natto).…”
supporting
confidence: 79%
“…and PaiA (Forouhar et al, 2005), have been reported from B. subtilis 168 to be components of a putative spermidine/spermine acetyltransferase (SSAT) that could initiate polyamine degradation via acetylation. The genes encoding SSAT (bltD and paiA) are not essential for B. subtilis 168 according to BSORF Bacillus subtilis genome database (http://bacillus.genome.jp/).…”
mentioning
confidence: 99%
“…Although acetylases belonging to the GNAT family play important roles in regulating gene expression in eukaryotes (22,33), there are few examples in which acetylases are known to influence gene expression in prokaryotes (10,41). Perhaps CgrB acetylates either CgrA or CgrC to promote its activity.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of Bacillus subtilis PaiA protein has recently been determined, and the protein was found to belong to the GNAT family and to have polyamine N 1 -acetyltransferase activity (30). Amino acid sequences of PaiA and nine bacterial proteins of related sequence show little resemblance to SSAT-like proteins by BLAST comparisons, but a sequence and structure alignment of SSAT and PaiA is given in Fig.…”
Section: Channels In the Surface Of The Dimer Provide Functionally DImentioning
confidence: 99%